The GATA3 gene is involved in leprosy susceptibility in Brazilian patients - Medeiros, Priscila; Silva, Weber Laurentino da; Gimenez, Bruna Beatriz de Oliveira; Vallezi, Karen Bastos; Moraes, Milton Ozório; Souza, Vânia Niéto Brito de; Latini, Ana Carla Pereira (ScienceDirect, 2016)
Leprosy outcome is a complex trait and the host-pathogen-environment interaction defines the emergence of the disease. Host genetic risk factors have been successfully associated to leprosy. The 10p13 chromosomal region was linked to leprosy in familial studies and GATA3 gene is a strong candidate to be part of this association. Here, we tested tag single nucleotide polymorphisms at GATA3 in two case-control samples from Brazil comprising a total of 1633 individuals using stepwise strategy. The A allele of rs10905284 marker was associated with leprosy resistance. Then, a functional analysis was conducted and showed that individuals carrying AA genotype express higher levels of GATA-3 protein in lymphocytes. So, we confirmed that the rs10905284 is a locus associated to leprosy and influences the levels of this transcription factor in the Brazilian population.
Keywords: Association study; GATA-3 transcription factor; GATA3; Leprosy; Polymorphisms; rs10905284